Examining the impact of the Good Behaviour Game on emotional and behavioural problems in primary school children: A case for integrating well-being strategies into education. Issue 3 (November 2019) - Torok, Michelle; Rasmussen, Victoria; Wong, Quincy; Werner-Seidler, Aliza; O'Dea, Bridianne; Toumbourou, John; Calear, Alison
Childhood emotional and behavioural problems can indicate a higher risk of developing mental illness in adolescence and beyond. Schools provide an appropriate setting in which to deliver universal preventions to improve well-being and protect against early risks for mental health disorder. However, interventions can often be difficult to implement in schools due to their perceived or actual burdensomeness and implementation challenges can affect effectiveness. Teacher-delivered well-being interventions that can be integrated into usual classroom teaching practices provide a potential solution. This study examines the efficacy of a teacher-delivered programme, the Good Behaviour Game, in Australian primary schools. The programme significantly reduced emotional and behavioural problems as measured by the Strengths and Difficulties Questionnaire from baseline to post-intervention, suggesting that it may be an effective teaching practice for managing students in the classroom and for promoting well-being and development.